Extreme environment interconnects and packaging for power electronics. Issue 17 (15th April 2019) - Campos‐Zatarain, Alberto; Hinton, Jack; Mirgkizoudi, Maria; Li, Jing; Harris, Russell; Kay, Robert W.; Flynn, David
Abstract : This paper presents the combination of an innovative assembly and packaging process utilising solid liquid inter diffusion (SLID) Cu‐Sn interconnects within bespoke ceramic substrates that have been produced using additive manufacturing (AM). The resultant process chain supports the integration and packaging of power electronics for harsh environment applications. Here, the authors explore how the bond strength and composition of Cu‐Sn SLID interconnects vary during exposure to thermal‐mechanical load profiles. Samples of Cu‐Sn are exposed to thermal loading up to 300°C and integrated mechanical loading via high random frequency vibrations (1 and 2000 Hz). In parallel, micro‐extrusion printing methods in which high‐viscosity ceramic pastes are dispensed through cylindrical fine nozzles (2–250 µm) using CNC‐controlled motion has enabled complex 3D geometries to be fabricated. Additional secondary conductor deposition after firing the ceramic substrate enables the electronic circuitry to be generated without dedicated tooling, masks, or templates. This work presents the first fully 3D‐printed ceramic‐based electronic substrates. To demonstrate the applications of this printing method, a 555 timer circuit with flashing LED has been printed and the components surface mount assembled. The resultant ceramic substrates are dense, mechanically robust, and the reflowed circuit functions exactly as intended.